Zombie firms and corporate innovation: a double distortion effect—empirical evidence from China. Issue 4 (23rd February 2023) - Yu, Xiaolin; Wu, Fan; Wan, Kai; Chang, Tsangyao
ABSTRACT: With China's entering into the era of high-quality development, we have studied in this paper whether and how the so-called 'zombie firms' have inhibitory impact on the quantity and quality of corporate innovation in normal enterprises. Using the 1998–2013 Chinese industrial database as the empirical evidence, we find that the inhibitory impact is significant, and particularly imminent for those normal enterprises with high innovation intensity under further inspection of heterogeneity test. Impact mechanism test indicates two major channels through which the inhibitory impact manifests: competition distortion and financing constraints. Our study not only clarifies the impact of zombie firms on the quantity and quality of corporate innovation, but also provides both theoretical and empirical reference for policymakers in China to properly address the problems of zombie firms and promote high-quality corporate innovation.